Treatment of Head and Neck Injuries in the Helmeted Athlete. Issue 3 (1st March 2016) - Diduch, B. Kent; Hudson, Korin; Resch, Jacob E.; Shen, Francis; Broshek, Donna K.; Brady, William; Cole, Steven L.; Courson, Ron; Castens, Titus; Shimer, Adam; Miller, Mark D.
Abstract : Sport-related concussion treatment includes three major phases: initial evaluation at the time of the injury, treatment while the patient is symptomatic, and evaluation of the readiness for a gradual return to participation. Each concussion evaluation should include similar elements: assessment of symptoms, assessment of cognitive ability, assessment of coordination (of the eyes, upper extremities, and lower extremities), and assessment for additional injuries. The spine-boarding recommendations from the American College of Emergency Physicians, National Association of EMS Physicians, and National Athletic Trainers' Association have changed. These recommendations include both decreased use of spinal immobilization and removal of the helmet and shoulder pads prior to securing the athlete to the board when sufficient numbers of trained providers are present. Preseason training and pregame meetings or "medical time outs" should become standard practice for the sidelines medical team (including the athletic trainer, team physician, emergency response personnel, and possibly others).